Pterostilbene increases Fas expression in T-lymphoblastic leukemia cell lines - Gelareh Ramezani; Batoul Pourgheysari; Hedayatollah Shirzad; Zahra Sourani (Wolters Kluwer Medknow Publications, 2019)
Treatment of acute lymphoblastic leukemia (ALL) has been promising in last decades, but side effects still persist and searching for the least toxic agents continue. Pterostilbene (PTE) is a natural compound with several anti-cancer and anti-oxidant properties. Fas, as a member of death inducing family of tumor necrosis factor (TNF) receptors with an intracellular death domain, can initiate the extrinsic apoptosis signaling pathway. Here after the half maximal inhibitory concentration (IC50) determination in cell lines, we searched for PTE effects on Fas, both in mRNA and surface levels in two ALL cell lines, Jurkat and Molt-4. After harvesting cells in optimum situations, MTS assay was used to determine IC50 concentrations. Real-time polymerase chain reaction (RT-PCR) and flow cytometry were performed for Fas mRNA and surface expression variations after exposure to PTE. The findings showed that PTE decreases cell viability with different extent in two ALL cell lines. In addition to inducing apoptosis, it can increase Fas in both gene and cell surface expression in the same concentrations. Pterostilbene as a natural anti-cancer agent can increase Fas expression both in mRNA and surface levels that results in apoptosis signal transduction improvement which sensitizes cells to apoptosis by immune effector cells. As a result, abnormal cells removal would be more efficiently with the minimum side effects on normal cells.